Reconstruction of Islamic Educational Thought between Tradition and Modernity in West Nusa Tenggara - Nur Ismiyahyi; Ahmad Barizi; Fadhilah Hanjani Putri; Fifin Nopisaputri (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to analyze the roots of Islamic tradition in West Nusa Tenggara (NTB), map the challenges of modernity facing local Islamic educational institutions, identify the typologies of ideological reconstruction, and examine the implications of these reconstruction models on contemporary educational policies and practices. The method employed in this qualitative research is a Systematic Literature Review (SLR) to identify, evaluate, and interpret scientific literature indexed in Sinta and Scopus, government regulations, and relevant scholarly books. The data analysis technique combines content analysis and thematic analysis through data reduction, thematic coding, categorization, and conclusion drawing. The research findings indicate that the traditional roots of Islamic education in NTB rest firmly on the dominance of bayani and irfani epistemologies through halaqah institutions, the charismatic authority of Tuan Guru, and local leadership manuscripts. The influx of modernity manifested in post-pandemic digital disruption, global tourism expansion, and national standardization has triggered institutional pressures and an epistemological dichotomy. The responses of religious institutions in NTB are classified into three reconstruction typologies:traditional-conservative, modernist-reformist, and integrative-transformative. The integrative-transformative model proves to be the most relevant adaptation pattern through the implementation of hybrid curricula, digitalization of learning media without desacralizing face-to-face learning, and character strengthening based on local wisdom. The practical implication of this reconstruction successfully transforms Islamic education in NTB into a living laboratory for contextualizing religious moderation while serving as a strategic pillar in maintaining cross-ethnic social cohesion.